Key Concepts in Politics
Concepts are the 'tools' with which we think, criticise, argue, explain and analyse. Political concepts are nothing less than the building-blocks of political understanding: the political world means what our concepts tell us it means. But political concepts are notoriously slippery and subject to controversy. Indeed, political debate is often a debate about the correct use of political terms. This book provides an accessible and comprehensive guide to the major concepts encountered in political analysis. Each is defined clearly and fully, and its significance for political argument and practice is explored. The introduction explains how political concepts are used and why they are so often abused. The book is arranged thematically, in an easy to use way, to be a vital companion for students throughout their course of study, and especially useful as a revision aid.